Prevalence of Hypertension Among Adolescents in Benue South, Nigeria - Rose, Okwunu Abah; Daniel, Ejeh Ukpabi; Juliana, Ajuma Okoko (Journal of Hypertension and Cardiology, 2025)
Background Hypertension in adolescents has been shown to tracks into adulthood, as well as causing premature cardiovascular and renal diseases. Objectives To determine the prevalence of elevated blood pressure and hypertension among adolescents of ages 10-19 years old attending secondary schools in Benue South, Nigeria; characterise their demographics and determine factors associated with the development of high blood pressure. Materials and Methods A cross-sectional descriptive study of secondary school adolescents selected through multistage sampling from across three Local Government Areas of Benue South, Nigeria. All the participants had their blood pressure measured using mercury sphygmomanometer and their height and weight taken for the calculation of their body mass index. A dipstick urinalysis with was carried out on their urine samples. Data analysis was with SPSS version 25. Results Atotal of 260 adolescents were studied, males were 132 (50.8%) and the mean age was 13.65 ±2.01 years. The prevalence of elevated blood pressure and hypertension was 5.4% and 2.3% respectively. Fifteen females (75.0%) had elevated blood pressure/hypertension as against five males (25%) and it was statistically significant. Adolescents in mid-adolescence age (60.0%) and lower social class (70.0%) had higher rate of high blood pressure. Significant proteinuria (+) was found among eleven (55.0%) of those with high blood pressure. Conclusion The prevalence of elevated blood pressure and hypertension among the adolescents was 5.4% and 2.3% respectively; being female, within mid-adolescence age and from lower social class are associated factors. Recommendation Regular blood pressure measurement should be part of school health programme.
Keywords: Adolescents; Elevated BP; Hypertension; Proteinuria